Safety and Feasibility of Regadenoson Use for Suboptimal Heart Rate Response During Symptom-Limited Standard Bruce Exercise Stress Test - Partington, Sara L. (2012)
BACKGROUND: Regadenoson during exercise stress test (ETT) can provide maximal hyperemia for myocardial perfusion imaging (MPI), along with exercise information. Our aim was to study the feasibility and safety of regadenoson injection at peak ETT for sub-maximal heart rate (HR) response. METHODS: Consecutive patients who underwent SPECT MPI with standard Bruce ETT or supine regadenoson (supine-Reg) were analyzed. ETT patients were grouped as ETT-Max [maximal HR >0.85* (220-age), N=1,522], ETT-Submax (submaximal HR no regadenoson, N=504), ETT-Reg (submaximal HR and regadenoson, N=211). RESULTS: The HR during ETT was submaximal in 715 (32%) patients. Of these, 211 patients (30%) underwent ETT-Reg (mean exercise duration: 5.5 ± 2.5 minutes). ETT-Reg patients had a higher frequency of hypertension, diabetes, smoking and beta-blocker use, similar rest systolic blood pressure (SBP), but lower rest and peak HR and peak SBP compared to ETT-Max patients. There were no serious complications with regadenoson. Side effects (49% vs. 6%, P<0.0001) were fewer and aminophylline use was lower with ETT-Reg compared to supine-Reg (.0.5% vs. 8.1%, P =0.001). CONCLUSIONS: Sub-maximal HR response to ETT is common. ETT-Reg is safe, feasible and well-tolerated. ETT-Reg facilitates a diagnostic MPI with reporting of functional capacity, exercise ECG/hemodynamic changes and MPI at maximal hyperemia.